KKK Komunikasyon at Kaugalian sa Klasrum : a multi-method study on the communication patterns between teachers and students inside the college classroom as a reflection of Filipino values - Encarnacion, Jewel G.; Silvestre, Sandra S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This multi-method study aims to look at the communication patterns between teachers and students inside the classroom and how these reflect Filipino values. Specifically, classroom communication patterns in five General Education (GE) classes are determined by finding out the different classroom communication activities conducted in these and which activities the teachers and students engage in. The motivations and language behavior of participants in the study are also taken into consideration. The immediacy of professors, the communication apprehension of students and the nonverbal codes used in interactions also make up the process of communication inside classrooms. It also dwells on how Filipino values are held by the study participants are reflected through classroom communication patters. To be able to fulfill the objectives of the study, the researchers made use of three research methods : Survey, Focus interviews and Participant-Observation. The results of the three methods were analyzed through the use of triangulation method. The research findings revealed that the personal backgrounds of participants affect their language preference. Through the use of nonverbal codes and communication apprehension, Filipino values manifest through interaction and thus affect classroom communication and involvement. The theories used for the framework of this study were appropriate in meeting the objectives of the research. The research methods were also appropriate for the study. However, the researchers the use of culture theories and the development of communication theories in the context of the Filipino since these may provide new insights on future studies regarding this subject.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Teacher-student relationships -- Values -- Filipino students